Senesens. Heart. Senotherapy - S. A. Kryzhanovskii; M. B. Vititnova (Фармакокинетика и Фармакодинамика)
Senescence — cellular aging — is a special form of cell death, characterized by the cell’s irreversible loss of its proliferation potential and the development of resistance to apoptosis. Senescence is based on the attrition (shortening) of telomeres that occurs with each subsequent cell division, which ultimately leads to sustained DNA damage and subsequent activation of the cellular aging program. Senescent cells have a unique so-called senescence-associated secretory phenotype (SASP), i.e. the ability of aging cells to secrete into the extracellular environment a large number of pathogenic factors that act paracrine on undamaged cells and transfer them to a state of senescence. The literature review examines the known mechanisms responsible for the formation of various types of senescence, describes the features of senescence-related cardiac damage, and provides a detailed description of biologically active compounds and drugs with senolytic (apoptosis activators) and/or senostatic (SASP inhibitors) activity.